Colagem e Ecosofia: entre fragmentos e composições na educação em ciências - Silva, Gabriella Pizzolante da (Universidade Federal de São Carlos, 2026)
This thesis produces and investigates the encounter between collage and ecosophy in science education, taking collage as a material, relational, and thought-based practice. It begins by problematizing modes of organization of school scientific knowledge that privilege representation, explanation, classification, and the stability of meaning, often separating body and thought, science and art, nature and culture, subject and world. Inspired by Félix Guattari’s ecosophy, by approximations with cartography, and by montage as an operation of thought derived from Georges Didi-Huberman, the research follows workshops with students from basic education, undergraduate teacher education, and graduate studies, an extension course, fabulated scenes, and artistic productions developed throughout the investigative process. The thesis is constructed through montages between not-so-invented memories, images, conceptual fragments, and formative experiences. By working with remnants, tears, displaced scientific images, dismantled textbooks, and collective compositions, the thesis follows what emerges when collage traverses stabilized ways of learning and organizing school scientific knowledge. In this movement, montage operates as a procedure that brings heterogeneous fragments together without reducing them to an explanatory unity, allowing knowledge production to be conceived through intervals, frictions, and provisional recompositions. As a contribution, the thesis proposes understanding collage as a situated ecosophical practice, capable of opening small recompositions between subjectivity, collectivity, and environment, tensioning ways of knowing and inhabiting educational spaces in science education.
Collage and Ecosophy: between fragments and compositions in science education
Keywords: colagem; collage; ecosofia; educação em ciências; arte; ciência; ecosophy; science education; art; science; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES PLASTICAS; 4. Educação de Qualidade